Nepal's Earthquake-2015: Its Impact on Various Sectors (The Gaze: Journal of Tourism and Hospitality, 2016)
Natural Calamities are unavoidable events that lead to chaos, crisis and disaster. Nepal faced a disastrous earthquake: 7.8 Richter scale. Being repeatedly analyzed about the vulnerability of earthquake in Nepal, the country seems not prepared enough for the event. The unpreparedness had taken many lives including tangible and intangible values of society and cultural aesthetics. The earthquake has hindered the overall economic, social and environmental aspect. Tourism was one of the major economic backbones for the nation which with the event has barred at least for sometimes. According to the survey conducted on the Tourism Employment by Ministry of Culture, Tourism and Civil Aviation (MoCTCA) indicates that approximately 138,148 persons were engaged in the tourism sector (National Planning Commission, 2015b: 118). The pre-earthquake data, indicates that 487,500 jobs which would be 3.5 percent of the total employment in Nepal. The number of jobs was expected to rise by 4 percent in 2015 and 3 percent per annum to 681,000 jobs (World Travel and Trade Council, 2015). According to World Health Organization, the epicenter of the earthquake was Barpakh, Gorkha and the magniturde of the earthquake has catastrophic effect on 14 district of Nepal, including Gorkha, Dhading, Rasuwa, Sndhupalchok, Kavre, Nuwakot, Dolakha, Kathmandu, Lalitpur, Khaktapur, Ramechap, Sindhuli, Okhaldhunga and Makwanpur districts out of which Dolakha and Sindhupalchok are the most severely affected districts by the second earthquake on 13 May, World Health Organization (WHO, 2015).The Gaze: Journal of Tourism and Hospitality Vol.7 2015 pp.58-86